Clinical researchBipolar versus monopolar technique for palliative transurethral prostate resection - Michielsen, Dirk P.J.; Coomans, Danny; Engels, Benedikt; Braeckman, Johan G. (Archives of Medical Science, 2010)
Introduction : The aim was to evaluate the postoperative morbidity and outcome of palliative endoscopic resections for relief of infravesical obstruction in prostate cancer patients with hormone deprivation therapy, and to investigate the added value of bipolar technology over conventional monopolar resections. Material and methods : A retrospective study was performed on 70 patients with prostate cancer under hormone deprivation therapy undergoing 75 endoscopic procedures, by either monopolar or bipolar technology, between August 2005 and March 2009 at a single institution. The analysis used outpatient, inpatient, and operative records, and observations of electrolyte changes in the serum, postoperative morbidity, and the overall results of palliative endoscopic resections. Preoperative cancer stages and grades were compared with the pathological findings after surgery. Postoperative outcome and complications of conventional monopolar and bipolar technology were compared. Results : Over a period of 44 months, 34 conventional monopolar resections were performed in 32 patients and 41 bipolar resections in 38 patients. Patients’ profiles regarding age, initial cancer stage and grade, resection weight, resection speed, catheterization time, and hospital stay were similar in both groups. No statistically significant difference was observed in sodium drop (p = 0.802), clot retention (p = 0.565), or urinary retention (p = 0.292). The overall success rate in relieving obstruction leading to spontaneous voiding was 77%. While 38% of the patients had a high grade tumour at diagnosis, 79% were found to be high grade after the endoscopic resection (p < 0.0001). Conclusions : Palliative endoscopic transurethral resection is an acceptable and safe adjunctive surgical treatment for voiding disorders in prostate cancer patients. Bipolar technology offers no substantial benefit over conventional monopolar technology.